2018
DOI: 10.1097/ccm.0000000000002752
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viruses in Invasively Ventilated Critically Ill Patients—A Prospective Multicenter Observational Study

Abstract: Respiratory viruses are frequently detected in acutely admitted and invasively ventilated patients. Rhinovirus and human metapneumovirus are more frequently found in severe acute respiratory infection patients. Detection of respiratory viruses is not associated with worse clinically relevant outcomes in the studied cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 24 publications
6
34
1
1
Order By: Relevance
“…33 Gréve et al reported 7 (0.5%) with hMPV and 21 (1.5%) with RSV among 1407 non-transplant patients admitted to the ICU on MV therapy in a prospective multicenter study in 2018. 11 Recent reports support our findings and indicate that hMPV and RSV should not be regarded as negligible pathogens and could be under-diagnosed in non-transplant critically ill patients, in particular on ventilated and ICU care. 11À13,16,34 However, we do not have any consensus that these CA-RVs are directly related to poor outcome and attributable mortality in this population.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…33 Gréve et al reported 7 (0.5%) with hMPV and 21 (1.5%) with RSV among 1407 non-transplant patients admitted to the ICU on MV therapy in a prospective multicenter study in 2018. 11 Recent reports support our findings and indicate that hMPV and RSV should not be regarded as negligible pathogens and could be under-diagnosed in non-transplant critically ill patients, in particular on ventilated and ICU care. 11À13,16,34 However, we do not have any consensus that these CA-RVs are directly related to poor outcome and attributable mortality in this population.…”
Section: Discussionsupporting
confidence: 88%
“…11À13,16,34 However, we do not have any consensus that these CA-RVs are directly related to poor outcome and attributable mortality in this population. 11,12,34 In addition, there is no standard guideline for prevention or treatment of CA-RVs among transplant recipients and non-transplant critically ill patients in ICU. Therefore, the guideline for indication of surveillance or diagnostic tests as well as treatment of specific CA-RVs in unique high-risk subpopulation through further prospective studies needs to be standardized to implement practices effectively.…”
Section: Discussionmentioning
confidence: 99%
“…A recently proposed clinical algorithm assessed the relevance of positive cultures and might be helpful for clinicians to decide whether to treat or not [50]. Finally, respiratory viruses including influenza, respiratory syncytial virus, and others may be responsible for VAP [51][52][53][54]. The Herpesviridae Herpes simplex virus (HSV) and Cytomegalovirus (CMV) can cause viral reactivation pneumonia in immunocompromised and nonimmunocompromised mechanically ventilated patients.…”
Section: Microorganisms Responsible For Vapmentioning
confidence: 99%
“…172 Rates of asymptomatic viral carriage range from 2 to 17%, depending on the patient population studied. 8,23,86,173 The specificity of PCR-based testing likely varies significantly, depending on both the age of the patient and the pathogen identified. 173 Further complicating testing is that results from upper and lower respiratory tract samples are frequently discordant.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…20 Other studies in ICU patients have reported viral infection rates between 18 and 41%. [21][22][23] Among patients with hematological malignancies admitted to the ICU, identification of a viral infection is independently associated with an increased risk of death and is more predictive of a poor outcome than preadmission performance status, organ failure score, or the Charlson comorbidity index. 24 Given the burden of noninfluenza respiratory viruses in CAP, it is important for clinicians to be familiar with the unique characteristics of the most commonly identified pathogens.…”
mentioning
confidence: 99%